Surgical treatment of lumbar canal stenosis with concomitant aggressive vertebral haemangioma - Kariya, Ankur D.; Jain, Pramod A.; Patond, Kisan R. (International Journal of Research in Orthopaedics, 2020)
Vertebral hemangiomas are the most common benign spinal tumours which are asymptomatic, slow-growing benign vascular malformations. They usually involve the vertebral body. However, the involvement of the posterior elements may present with spinal cord compression. Vertebral hemangiomas exist as a continuum of manifestations and lesions ranging from the common asymptomatic forms to rare compressive lesions. Presence of multilevel spinal canal stenosis along with an atypical vertebral hemangioma with cord is a rare condition and represents a treatment challenge. We report a case of spinal canal stenosis at L2 to L4 spinal levels along with an atypical vertebral hemangioma at L3 vertebra with extension to bilateral pedicles. This tumour caused neurological manifestations and was surgically treated with posterior decompression and stabilization with transpedicular screws and rods along with vertebroplasty for the hemangioma. Presence of an atypical hemangioma with co-existing spinal canal stenosis is a rare indication of spinal fusion. Vertebroplasty for the treatment of hemangioma in such cases is imperative.